A New Geological Map of the Marginal Basins of Eastern Papua New Guinea: Implications for Crustal Accretion and Mineral Endowment at Arc–Continent Collisions - Philipp A. Brandl; Mark D. Hannington; Anna Krätschell; Sven Petersen; Alan T. Baxter; Margaret S. Stewart; Christopher Galley; Justin Emberley; Sylvia G. Sander (Lithosphere)
Accretion of island arc terranes is a fundamental process of crustal growth and the formation of new continents. Convergent margin tectonics, both compressional and extensional, in accretionary orogens also control the origin and distribution of their contained mineral resources, including many of the world’s important Cu and Au deposits. However, the details of crustal growth and accretion are often lost because of deformation and selective preservation during subduction. The Melanesian Borderland, which includes the offshore regions of eastern Papua New Guinea and the Solomon Islands, contains several active and relict arc and backarc systems that have formed in response to more than 50 Ma of subduction and complex plate tectonic adjustments. The composite terrane is a region of some of the fastest growing crust on Earth and also spectacular mineral endowment, including three of the top ten porphyry Cu and epithermal Au deposits in the world. However, more than 80% of the belt is submerged, and so little is known about its geological evolution and makeup. Here, we present the first detailed geological map of the region in one map sheet, including the marginal deep ocean basins. The map identifies and groups the key lithostratigraphic formations and correlates associated tectonic events across the belt. The final compilation is presented at 1:1,000,000 scale, which is sufficient to allow quantitative analysis of crustal growth and accretion during ocean–continent collision throughout the region. The map shows the diversity of assemblages in accreting terranes that may eventually become part of a growing continent and highlights their complex formation and structural relationships. Because so much of that history has occurred offshore, the new map presents the first complete picture of the geology of the region in the critical period leading up to its eventual incorporation in the Australian continent.